Manual Ability Classification System (MACS): reliability between therapists and parents in Brazil - Daniela B. R. Silva (Revista Brasileira de Fisioterapia, 2015)
Background: The Manual Ability Classifi cation System (MACS) has been widely used to describe the manual ability of children with cerebral palsy (CP); however its reliability has not been verifi ed in Brazil. Objective: To establish the inter- and intra-rater reliability of the Portuguese-Brazil version of the MACS by comparing the classifi cations given by therapists and parents of children with CP. Method: Data were obtained from 90 children with CP between the ages of 4 and 18 years, who were treated at the neurology and rehabilitation clinics of a Brazilian hospital. Therapists (an occupational therapist and a student) classifi ed manual ability (MACS) through direct observation and information provided by parents. Therapists and parents used the Portuguese-Brazil version of the MACS. Intra- and inter-rater reliability was obtained using unweighted Kappa coeffi cient (k) and intra-class correlation coeffi cient (ICC). The Chi-square test was used to identify the predominance of disagreements in the classifi cation of parents and therapists. Results: An almost perfect agreement resulted among therapists [K=0.90 (95% CI 0.83-0.97); ICC=0.97 (95%CI 0.96-0.98)], as well as with intra-rater (therapists), with Kappa ranging between 0.83 and 0.95 and ICC between 0.96 and 0.99 for the evaluator with more and less experience in rehabilitation, respectively. The agreement between therapists and parents was fair [K=0.36 (95% CI 0.22-0.50); ICC=0.79 (95% CI 0.70-0.86)]. Conclusions: The Portuguese version of the MACS is a reliable instrument to be used jointly by parents and therapists.